Colorindo conversas e desenhando histórias: experiências de crianças e adolescentes com doença falciforme na Paraíba - Pimentel, Bruna Tavares (2020)
The present study addresses the experience and conceptions of children and adolescents about sickle cell disease. “Sickle cell anemia” as it is known, is a genetic disease that carries the race marker, since the black population is the most affected. This is a study carried out with affected children and adolescents from the state of Paraíba, whose parents / guardians are members of Associação Paraibana de Portadores de Anemias Hereditárias (ASPPAH). The association was the mediating institution in the access to the participants of the research, carried out in four cities: João Pessoa, Campina Grande, Areia and Santa Rita. Methodologically, the dialogue with the interlocutors took place during the production of drawings, in the case of children, and of semi-structured interviews with the adolescents. Through this approach it was possible to build, identify and analyze elements of meaning and meaning attributed to their experiences with the disease, allowing us to understand the view of children and adolescents about the disease, experience of the disease, self-care learning learned from parents and / or responsible, as well as the main complaints related to restrictions such as: not being able to bathe in the rain, not going out in cold weather and restrictions on the use of some clothes. For children, the disease affects their lives in different social contexts, such as the school environment, and their experiences in the hospital environment. Finally, they pointed to prejudice, school absences, hospital environments recurrence and limitations in children's play relationships